Identifikasi Serangga Hama Dan Penyakit Pada Tanaman Jagung Pulut (Zea mays ceratina) Di Unit Pelaksana Teknis Pengembangan Agribisnis Tanaman Pangan Dan Hortikultura Sidoarjo - Vivin Andriani; Lathifatul Azmi Ar Rohmah; Eko Sugandi (STIGMA: Jurnal Matematika dan Ilmu Pengetahuan Alam Unipa, 2025)
Waxy corn (Zea mays ceratina) is one of the corn varieties with high potential to be developed as an alternative food source due to its high amylopectin content, which gives it a soft and sweet texture. However, the productivity of waxy corn in Indonesia remains low due to various cultivation constraints, particularly pest and disease attacks that can cause significant yield losses. Identification of pest and disease species is essential as an initial step in developing effective and sustainable control strategies. This study aimed to identify the types of insect pests and diseases attacking waxy corn plants at the Technical Implementation Unit for the Development of Food Crop and Horticulture Agribusiness (PATPH) in Sidoarjo, East Java. The research was conducted from February to March 2024 using a simple random sampling method on four plots ranging from 15 × 20 m² to 20 × 20 m². Observations were made on symptoms of pest and disease attacks, which were then identified based on morphological characteristics and symptom similarities with reference literature. The results showed three types of pests attacking waxy corn, namely armyworms (Spodoptera litura), hairy caterpillars, and grasshoppers, with a total of 14 individuals recorded. Meanwhile, five major diseases were found—leaf blight (Helminthosporium turcicum), leaf rust (Puccinia polysora), leaf spot (Bipolaris maydis), downy mildew (Peronosclerospora maydis), and corn smut (Ustilago maydis)—infecting a total of 158 plants. The intensity of pest attacks tended to decrease during the generative phase, while leaf diseases increased with plant age due to microclimatic changes and higher humidity under the canopy. Based on these findings, leaf diseases, particularly rust and leaf spot, were identified as the main limiting factors of waxy corn productivity. Therefore, the implementation of Integrated Pest Management (IPM) and the use of disease-resistant varieties are necessary to improve yield and ensure sustainable cultivation.   Keywords: waxy corn; pests; diseases; UPT PATPH